Challenging a ‘Warist’ Society with Digital Peace Pedagogy - Foster, J. Ashley; Janco, Andrew (Radical Teacher, 2020)
This article offers strategies for a peace pedagogy that is informed by combining techniques from feminist theory and peace studies with the digital humanities. Here we describe how the first-year Writing Seminar “Peace Testimonies in Literature & Art,” taught in Spring 2017 at Haverford College, collaborated with the activist organization the American Friends Service Committee (AFSC) to participate in the collection and curation of oral histories projects. In this class, students conducted oral history interviews of peace activists at the 2017 AFSC symposium “Waging Peace: AFSC’s Summit for Peace and Justice” (April 20-23 in Philadelphia, PA), and then analyzed the videos of these interviews through OHMS (Oral History Metadata Synchronizer) and the video editing software Camtasia. Here we discusses how feminist, digital, and peace pedagogies can be combined to help students recover the lost histories of pacifist activism.